Perfil laboratorial bioquímico e hematológico de uma população de pacientes diagnosticados com hanseníase: antes e durante a poliquimioterapia - Silveira, Maria Irismar da Silva (2007)
Leprosy or Hansen’s disease is an infectious disease with slow flow velocity, transmitted by Mycobacterium leprae that attacks nerves and skin. The specific treatment for people who suffer of leprosy was emphasized in the beginning of the 80’s by the World Health Organization (WHO) in order to cure the infection with Mycobacterium leprae and prevent disability. The WHO has implemented a multidrug therapy (MDT) composed of dapsone, rifampicin and clofazimine, an association that prevents bacillus resistance. The MDT kills the bacillus, prevents the aggravation of the disease, and if followed precisely, guarantees the cure of the disease. The objective of this study was to evaluate laboratory parameters, before and during the MDT, in a population of 102 hansenian patients, aged 5 to 78 years, diagnosed and assisted at the Center of Dermatology Dona Libânia (CDERM) between January 2005 and January 2006. Evaluation of liver function (GOT, GPT, total bilirubin and fractions and alkaline phosphatase), renal function (urea and creatinine) and haematological parameters (leukogram, hematocrit and hemoglobin) was done through blood serum analysis or patient’s clinical history. A review of patient’s medical records as well as blood tests was done before treatment, after 6 months and after one year. A total of 102 patients participated on the study. Fifty patients (49%) were classified as paucibacillary (PB) and 52 (51%) multibacillary (MB). Social-demographic characteristics showed that 48 (47%) were female and 54 (53%) were male; 12 (11.7%) were either illiterate or have not finished the first grade; 6 (5,8%) were graduating; 40 (39.2%) did not have income and 34 (33.3%) earned no more than the minimum wage. Mean age was 40,8 years (SD = 19,3) and the number of patients younger than 10 years was higher in PB. As to the clinical form, 32 patients (31.3%) presented the tuberculoid form, followed by dimorph (30.3%); dimorph / tuberculoid (14.7%); Virchowian (7.8%); dimorph / Virchowian (2.9%); and undetermined (1.9%). Hematological analysis showed that anemia was the most frequent alteration, being present before and during treatment, and was most significant in the group MB in the sixth month of treatment. The most frequent alterations showed in the leukogram before and during the MDT in both PB and MB groups were lymphocytosis and eosinophilia. Regarding to biochemical parameters, that changes in the levels of GOT (5.8%) and GPT (4.9%) without statistical significance. Considering the lack of a typical laboratory profile for leprosy, the changes found in some parameters during polychemotherapy can not be attributed only to adverse effects of this therapy but to other effects that are inherent to leprosy and the use of MDT. Therefore, a safe polychemotherapy requires the realization of laboratory tests before and during treatment.